Ethics and sustainability in hospitality employer branding - Vasco Santos; Patrícia Sim\~ao; Isabel Reis; Marta Correia Sampaio; Filipa Martinho; Bruno Sousa (Administrative Sciences, 2023)
Tourism is currently one of the main sectors of profit for the worldwide economy. This study aims to explore ethics and sustainability in employer branding applied in the hotel industry, which is intended to correlate these very current and little-explored themes. This study aims to explore the investigation of these concepts that have grown, especially in the area of tourism and hospitality, as a way to better understand how the hotel sector can improve and develop strategic tools to achieve organisational success and capture the best talent. Methodologically, a Delphi method (three rounds) was performed through 26 participants recognised as experts of three major associations within the hotel industry in Portugal. As the main outcome, this research validated the Ethics and Sustainability in Hospitality Employer Branding Model, comprising three dimensions (HRM and EB Practices; Factors of business ethics and environmental sustainability; and Advantages of UH in implementing the EB strategy and RS communication) and underlying categories. Findings and practical implications to management are presented.
Keywords: 350; tourism; hospitality; ethics; sustainability and employer branding